OXTR rs2254298 polymorphism influences escitalopram response in Generalized Anxiety Disorder: a sex-specific role for oxytocin signaling - Xue, Liang; Ni, Hongfen; Dai, Hong (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to investigate whether the functional OXTR rs2254298 polymorphism moderates escitalopram response in Generalized Anxiety Disorder (GAD) through oxytocin (OT) neuroendocrine signaling, with specific consideration of sex-specific effects.Methods88 patients with GAD and 92 matched healthy controls (HCs) were enrolled. All participants underwent OXTR rs2254298 genotyping and baseline serum OT measurement. GAD patients then received 8 weeks of escitalopram monotherapy. Anxiety severity was assessed using the Hamilton Anxiety Scale (HAMA) at baseline and weeks 2, 4, and 8.ResultsBaseline serum OT levels were significantly elevated in GAD patients compared to HCs (126.28 ± 88.41 vs. 92.77 ± 47.51 pg/mL, p = 0.006), a difference that was primarily driven by female patients (p = 0.037). OT levels were positively correlated with baseline HAMA scores (r = 0.197, p = 0.008). After 8 weeks of treatment, the OXTR rs2254298 genotype distribution significantly differed between treatment responders and non-responders (p = 0.049), with GG homozygotes showing a lower response rate.ConclusionOur findings suggest that the OXTR rs2254298 polymorphism may influence escitalopram response in GAD via OT neuroendocrine mechanisms, exhibiting prominent sexual dimorphism. Integrating genetic profiling with endocrine biomarkers holds promise for personalizing anxiety treatment.